Recovery-Oriented Systems of Care (ROSC): understanding individual and system-level barriers and facilitators to implementation of ROSC in an addictions treatment community - Conner, Stacy R. (Kansas State University, 2017)
Addiction to mood-altering substances i.e., drugs and alcohol is a public health concern impacting society in many contexts (e.g., employment, financial costs, family welfare, healthcare, and criminal activity). As a result of the substantial personal and societal costs associated with substance abuse, significant federal dollars have been spent on addiction recovery services in an attempt to ameliorate the negative impacts of these disorders. Like many chronic diseases, relapse (40-60%; National Institute on Drug Abuse, 2012) and dropout (23-50%) rates for clients in drug and alcohol outpatient treatment tend to be high (McHugh et al., 2013; Santonja-Gomez et al., 2010; Evans, Li, and Hser 2009; Stark, 1992). Over time, it has become clear that a single course of treatment is simply not enough to meet the needs of a person in recovery from alcohol and/or other drug abuse. The field of addiction treatment and recovery has been dominated by an acute-care model of treatment. A new model, recovery-oriented systems of care (ROSC), defined as “networks of organizations, agencies, and community members that coordinate a wide spectrum of services to prevent, intervene in, and treat substance use problems and disorders” (Sheedy & Whitter, 2013, p. 227), has been endorsed by the Substance Abuse and Mental Health Services Administration (SAMHSA) and the Center for Substance Abuse Treatment (CSAT). As communities begin to implement ROSC it is imperative to understand the barriers to transitioning out of the traditional, acute-care model. Findings from in-depth qualitative interviews revealed that both treatment and probation professionals described more alignment with the ROSC model than the acute-care model. For treatment professionals, this alignment was stronger at an individual level and for probation professionals it was stronger at the system level. For both professional groups, the system-level barriers to moving toward a ROSC model were much greater than any individual-level barriers. Facilitators were found evenly split for the most part between individual and system level codes. For communities making movement toward the ROSC model, the systems of treatment and probation have great potential at the individual level for ROSC alignment and have available facilitators for overcoming system-level barriers in place. Although the acute-care model served a purpose at one time, it is now time for the ROSC model to be implemented as a comprehensive response to addiction and needs in recovery.
Keywords: Recovery-oriented systems of care; Substance use treatment; Probation; Addiction; Acute-care; Recovery